Parthenium weed (Parthenium hysterophorus) competition with grain sorghum under arid conditions. (5th June 2020) - Bajwa, Ali A.; Nawaz, Ahmad; Farooq, Muhammad; Chauhan, Bhagirath S.; Adkins, Steve
Abstract: Parthenium weed is an invasive species in a growing number of countries where it infests numerous crop fields, including sorghum. Two field studies were conducted to quantify the effect of parthenium weed on the performance of grain sorghum at different weed densities (0, 5, 10, 15 and 20 plants m −2 ) and durations of weed-crop competition (season-long weed-free, weed-free after 2, 4, 6 or 8 weeks, and season-long weedy). Our aim was to identify the density threshold and ideal duration to control parthenium weed in sorghum fields. Both field experiments were planned in a randomised complete block design each with three replications in 2016 and were repeated in 2017. Parthenium weed biomass increased significantly with increasing density and competition duration. The increasing parthenium weed density had a linear negative effect on sorghum growth, yield and yield-contributing traits. The highest yield loss, of up to 66%, was recorded at the highest parthenium weed density of 20 plants m −2 when compared to weed-free treatment. In addition, the season-long competition of this weed with sorghum caused 81% reduction in grain yield over weed-free treatment. According to our results, parthenium weed should be managed below a density of 5 plants m −2 and throughout the crop growth duration in grain sorghum fields as it can cause serious yield losses even at low densities and through strong competition at early as well as late growth stages of the crop.